Needs Analysis of Website Development as Marketing Media to Support SDG 8 for Furniture Entrepreneurs in Petekeyan Village, Jepara Regency - Jayanti Putri Purwaningrum; Nur Fajrie; Evana Andriani; Jati Widagdo (Journal of Current Studies in SDGs, 2027)
Objective: The study aims to analyze the need for website development as a digital marketing medium for furniture entrepreneurs in Petekeyan Village, Jepara Regency, to support business competitiveness and sustainable economic growth in line with SDG 8. Method: The study employed a quantitative descriptive approach. Data were collected through questionnaires and semi-structured interviews with furniture business owners in Petekeyan Village, Jepara Regency. The collected data were analyzed descriptively to identify entrepreneurs' perceptions and functional requirements for website-based marketing. Results: The findings revealed that 67% of business owners strongly agreed that a website is essential for improving product marketing and expanding market reach. The most expected website features include user login and registration, social media integration, high access speed, data security, accessibility, scalability, backend system integration, and reporting and analytics functions. These features reflect the practical needs of entrepreneurs in adopting digital marketing strategies. Novelty: The study provides an empirical needs analysis for developing a website tailored to the requirements of furniture entrepreneurs in Petekeyan Village. Unlike previous studies that primarily evaluate website implementation, this research identifies user-driven functional requirements as the foundation for designing an effective digital marketing platform that supports business digitalization and contributes to the achievement of SDG 8 (Decent Work and Economic Growth).